Leadership and corporate culture: A quantitative analysis of strategies for designing specific cultures within companies of the future - Smith, Sarah Christina (The IIE, 2020)
An effective leader needs to understand the goals and purposes of employees. The study narrowed its focus onto the influence that leadership has on the development of corporate cultures within organisations. The purpose of the study was to validate the growing need for positive cultural experiences facilitated by the leaders of an organization and to further determine if a strong corporate culture plays an important role in developing a sustainable and inviting ethos for both current and future employees. The research problem was that where an organization fails to implement specific cultural design the company culture will form by default. A lack of leadership in developing the corporate culture results in employees feeling less important within their organizational role and therefore the organization will face a loss in productivity, inconsistent work ethic and employee dissatisfaction. Culture and self-worth are increasingly becoming an integral part of an individual’s job satisfaction and as a result directly impacts their performance thus impacting the overall success of the organisation. In order to consider this relationship the literature on leadership theories and styles, components of corporate culture, the creation and maintenance of corporate culture, culture fit, and the performance of employees was considered. The study followed a quantitative approach and made use of questionnaires to collect data which was then analysed through the use of SPSS. The research findings demonstrated that respondents had a higher tendency to agree with statements that suggested that leadership was vital for the development of corporate culture within organisations, and went further as to agree that this relationship can impact both the individual and the organisation as a whole.
Keywords: Leadership; Corporate culture; Culture design; Companies of the future